A Study on Effect of Problem solving on student's achievement - Dannawi, Dana Musbah (2013)
The investigation is about the importance of teaching problem solving and critical thinking in schools and including it in the curriculum, to prepare students achieve the best quality of thinking in the society and be more involved in the society. The study focuses on the gender difference and the use of cooperative learning in teaching problem solving, how it affects on their performance. The study was on 10th graders in U. A.E., Dubai private school, under the implementation of cooperative learning. A comparative data collected by pre-test and a post-test to study the student's achievement as well as a questionnaire to study the cultural background of the students. The study showed there is significance in performance in aspects, gender and student's achievement, but no significance in culture.